OPTIMASI TEKNOLOGI DIGITAL UNTUK PEMASARAN PRODUK UMKM MELALUI INTEGRASI LANDING PAGE DAN WHATSAPP BUSINESS - El Hasan, Qona'ah; Mahsyar, Januar Habibi; Muttaqien, Dadan Darmawan; Setiyadi, Adit (STAI Darul Qalam Tangerang, 2025)
The use of digital technology in marketing is becoming increasingly important for MSMEs to compete and thrive in the digital economy era, but some MSMEs face challenges in utilizing digital technology effectively. One effective strategy is the use of landing pages and WhatsApp Business, which can provide ease of communication and increase direct customer engagement. The landing page serves as a center of information and promotion, while WhatsApp Business facilitates direct communication with customers. This integration is expected to increase marketing efficiency, expand market reach, and improve interaction with customers. This article is the result of community service activities carried out in Kadugede Village, Kuningan Regency, with the aim of assisting MSMEs in utilizing landing pages integrated with WhatsApp Business to strengthen their digital marketing strategies. The method used in this activity is training/workshop, which involves participants actively in the process of creating and integrating the two platforms. The results of this activity showed that the participants were able to create a landing page and integrate WhatsApp Business well, thus helping to promote MSME products more widely. This shows that the utilization of digital technology such as landing pages and WhatsApp Business can be an effective strategy in improving marketing by expanding the market reach and sales of MSMEs. This training also has a positive impact on increasing the digital literacy of MSME players.